Sistem Manajemen Risiko Berbasis ISO 31000 : 2018 di PT. Bawen Mediatama - Gerardus Kevin Geofanny (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Risk is a situation that contains an element of uncertainty and is sometimes associated with the possibility of events that can threaten the achievement of organizational goals and objectives. The risk must be managed, because the losses arising from the risk can be very large. The purpose of data collection is to find out what risks will occur during the printing process at PT. Bawen Mediatama. This study uses qualitative methods with descriptive data presentation. Data collection techniques using direct observation and interviews. Data analysis techniques in the field were carried out through several stages, namely: data collection, data reduction, data presentation, and drawing conclusions. This study found that the risk of work accidents at PT. Bawen Mediatama can be categorized into 4 types, namely: risk identification, risk analysis, risk evaluation, and risk treatment. This study also found that using ISO 31000 can be seen the value of risk with low, medium, and high risk levels.